PENGARUH STRES KERJA, WORK-LIFE BALANCE, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN ALFAMART DI KABUPATEN PURWOREJO - Mochammad Zidan; Hardin; Fitri Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of work stress, work-life balance, and workload on the performance of Alfamart employees in Purworejo Regency. This study employed a quantitative approach using a survey method and an associative research design. The population consisted of operational employees of Alfamart outlets in Purworejo Regency, with a sample of 100 respondents determined through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 25.0. The results indicate that work stress has a negative and significant effect on employee performance (t = -2.318; sig = 0.023), work-life balance has a positive and significant effect on employee performance (t = 6.372; sig = 0.000), and workload has a negative and significant effect on employee performance (t = -2.347; sig = 0.021). Simultaneously, the three independent variables significantly affect employee performance (F = 18.944; sig = 0.000) with a coefficient of determination of 0.372, indicating that work stress, work-life balance, and workload explain 37.2% of the variance in employee performance, while the remaining 62.8% is explained by other variables outside this research model. These findings imply that Alfamart management needs to give proportional attention to work stress management, work-life balance support, and workload distribution among employees in order to sustainably improve performance.